Reply to the comments by Tarkan Erdik and Zekai Şen on 'A comparative study of ANN and neuro-fuzzy for the prediction of dynamic constant of rockmass' - Singh T.N.; Kanchan R.; Verma A.K.; Saigal K. (My University, 2025)
[No abstract available]